Treatment of spontaneous intracerebral haemorrhage with tranexamic acid - Law, Zhe Kang (2019)
Spontaneous intracerebral haemorrhage is a devastating condition with high morbidity and mortality. Haematoma expansion and subsequent secondary brain injuries lead to worse outcomes in intracerebral haemorrhage. Tranexamic acid is a promising haemostatic agent that may prevent haematoma expansion and improve outcomes. The current thesis explores the effects of tranexamic acid in intracerebral haemorrhage from clinical, radiological and biochemical aspects, based on data from the now completed Tranexamic acid in IntraCerebral Haemorrhage-2 (TICH-2) trial.